Antifungal properties of Piper betle leaf extracts against Malassezia furfur and Trichophyton rubrum - Rabiatul Adawiyah Umar
Malassezio furfur and Trichophyton rubrum are the most prevalent agents of fungal skin infections. They have been reported to cause widespread and invasive infections in immunocompromised individuals. Treatment with currently available antifungal agents may lead to severe side-effects and emergence of resistant strains. Previous studies have revealed that Piper betle leaf extracts have significant antifungal properties. However, till date the extensive reports on their antifungal properties against these fungi are still inadequate. This study aims to evaluate the antifungal properties of P. betle leaf extracts against M. furfur and T. rubrum and to study their effects on the morphology of the fungi as part of the study of their mechanisms of action as an antifungal agent. P. betle leaves were extracted using polar (n-Hexane), semipolar (dichloromethane) and nonpolar (ethanol) methods. The antifungal properties of all extracts were evaluated using disc diffusion and broth dilution methods. The inhibition zone diameter was measured and the Minimal Inhibitory Concentration (MIC) and Minimal Fungicidal Concentration (MFC) were determined. Folin-Ciocalteu and aluminium chloride colorimetric assays were used to estimate the total phenolic acids and flavonoids contents of the extracts. The presence of gallic acid and quercetion compounds were also studied using High Performance Liquid Chromatography (HPLC). Morphological changes of the treated fungi were studied using scanning electron microscope (SEM). All types of extracts exhibited antifungal properties against the fungi. The polar ethanolic extract of the P. betle leaves has the highest antifungal properties whereby at the concentration of 1.25 mg/mL and 2.5 mg/mL, 13.00 ± 0.00 mm and 11.00 ± 0.10 rom in diameter zone of inhibition were recorded for M. furfur and T. rubrum respectively. This results were in line with the MIC and MFC values of the extract; M. furfur (MIC: 1.25 mg/mL, MFC: 5.00 mg/mL) and T. rubrum (MIC: 2.5 mg/mL, MFC: 10 mg/mL). Polar ethanolic extract was also found to have the highest amount of total phenolic acids (20.77 ± 0.15 mg OAE/g) and flavonoids (64.50 ± 0.65 mg CE/g) contents. The presence of gallic acid and quercetin compounds were detected in ethanolic and dichloromethane extracts. Morphological study showed that the treated M. furfur cells were shrunken; having rough membrane surfaces and presence of decomposing cells were noted. T. rubrum hyphae were found to be flattened, emptied and necrotic. P. betle leaves extracts possess significant antifungal properties against M. furfur and T. rubrum and could potentially be the alternative therapeutic agents against these two fungi.